The effect of vitamin D supplementation on muscle soreness and recovery after exercise: A systematic review and meta-analysis - Fatemeh Kazeminasab; Ali Bahrami Kerchi; Fatemeh Sharafifard; Nafiseh Hasanpour (مجله علوم پزشکی فیض (پیوسته), 2024)
Background and Aim: Vitamin D has been shown to reduce exercise-induced muscle damage and muscle soreness; however, further research is needed to establish definitive conclusions. The aim of this study was to investigate the effect of vitamin D supplementation on muscle soreness and recovery after exercise. Methods: A systematic review and meta-analysis was conducted to evaluate the effects of vitamin D intake on muscle soreness and biochemical markers of muscle damage, including myoglobin (MB), creatine kinase (CK), lactate dehydrogenase (LDH), and inflammatory factors such as TNFα and IL-6. Data were sourced from PubMed, Scopus, and Web of Science databases up to February 2024. Analyses were performed to compare vitamin D with placebo, and weighted mean differences (WMD) were calculated. Results: A total of 11 studies involving 358 athletes and non-athletes were examined. Changes in muscle soreness immediately after exercise due to vitamin D intake were not statistically significant [P=0.70, WMD=-0.07]. However, vitamin D significantly reduced muscle soreness 24 hours after exercise [P=0.04, WMD=-0.40]. No significant changes were observed in CK [P=0.30, WMD=-3.22 U/L], LDH [P=0.30, WMD=-11.86 U/L], or MB [P=0.50, WMD=10.66 ng/ml] immediately after exercise. Conclusion: Vitamin D may be effective in reducing muscle soreness 24 hours post-exercise, but it does not appear to significantly affect markers of muscle damage, including CK, MB, and LDH, in the timeframes studied. Further research in this area is recommended.